2012
DOI: 10.1007/s11422-011-9374-y
|View full text |Cite
|
Sign up to set email alerts
|

Effective practices for creating transformative informal science education programs grounded in Native ways of knowing

Abstract: There are a growing number of informal science education (ISE) programs in Native communities that engage youth in science education and that are grounded in Native ways of knowing. There is also a growing body of research focusing on the relationship between culture, traditional knowledge, and science education. However, there is little research documenting how these programs are being developed and the ways in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
5
27
0
1
Order By: Relevance
“…Finally, like Mack et al (2011) our work would support their findings that it is challenging finding community members who hold culturally traditional knowledge with an understanding of scientific knowledge.…”
Section: Educational Importance Of This Studysupporting
confidence: 67%
See 2 more Smart Citations
“…Finally, like Mack et al (2011) our work would support their findings that it is challenging finding community members who hold culturally traditional knowledge with an understanding of scientific knowledge.…”
Section: Educational Importance Of This Studysupporting
confidence: 67%
“…Both our work and the findings of Mack et al (2011) are particularly relevant for Indigenous groups where learning and knowledge is traditionally integrated throughout disciplines, and is locally derived and reflective of what is useful and practical in a specific place. We both discovered that teacher autonomy was a huge component of program success and acknowledge the role of culture in motivating and helping students recognize the difference between worldviews.…”
Section: Educational Importance Of This Studymentioning
confidence: 87%
See 1 more Smart Citation
“…Garibay (2009), for example, found people from Latino communities in the USA felt ISE institutions were unwelcoming and the lack of representation of their own cultures and languages was particularly problematic since this led to a sense that ISE was not culturally relevant for them. Research carried out elsewhere, for example, an interview study with female Māori scientists in New Zealand exploring early experiences of science (McKinley, 2008), a study of a series of ISE programmes in Native communities in the USA (Mack et al, 2012) and a qualitative study of a multicultural ISE programme with Jewish and Arab students in Israel (Tal & Alkaher, 2010), found that people from non-dominant backgrounds struggled with ISE experiences that felt culturally distant or irrelevant. Taken together these studies suggest that across different contexts, different groups struggle to see ISE and ISE institutions as culturally relevant because of the issues to do with power, language, content and representation.…”
Section: Redistribution and Recognition In Ise Infrastructure Accessmentioning
confidence: 99%
“…As Mack et al (2012) note, Indigenous environmental science education is a rapidly expanding area of theory, research and practice in North America and internationally. As the field develops, several issues are rising in the literature as common points of discussion and debate.…”
Section: Integration: a Controversial Conceptmentioning
confidence: 99%